Relationship of Leadership Style and Achievement Motivation to Productivity of Training and Education Participants of Community Learning Activity Center in North Sulawesi - Wullur, Mozes M.; Pinontoan, Marien; Wullur, Ivan S.G. (Abdurrauf Science and Society, 2025)
This institutional research aims to analyze and describe the relationship between leadership style and productivity; achievement motives and productivity; and leadership style and achievement motives simultaneously with the productivity of North Sulawesi PKBM training participants. The results of the study are that there is a significant relationship between leadership style and productivity; achievement motives and productivity; and leadership style and achievement motives simultaneously with the productivity of North Sulawesi PKBM training participants.